2018
DOI: 10.1186/s12866-018-1189-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput analysis of Yersinia pseudotuberculosis gene essentiality in optimised in vitro conditions, and implications for the speciation of Yersinia pestis

Abstract: BackgroundYersinia pseudotuberculosis is a zoonotic pathogen, causing mild gastrointestinal infection in humans. From this comparatively benign pathogenic species emerged the highly virulent plague bacillus, Yersinia pestis, which has experienced significant genetic divergence in a relatively short time span. Much of our knowledge of Yersinia spp. evolution stems from genomic comparison and gene expression studies. Here we apply transposon-directed insertion site sequencing (TraDIS) to describe the essential g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…This confirmed that the genes are not essential for survival of Y. pseudotuberculosis under in vitro growth conditions, as suggested by our previously published TraDIS data [18].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This confirmed that the genes are not essential for survival of Y. pseudotuberculosis under in vitro growth conditions, as suggested by our previously published TraDIS data [18].…”
Section: Resultssupporting
confidence: 90%
“…pseudotuberculosis strain IP32953 was previously used to generate a transposon library of approximately 40 000 unique insertion mutants using the Ez-Tn 5 Kan2 transposome complex (Epicentre) as described and validated by Willcocks et al . [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in pathogenic Streptococcus agalactiae , the core genome constitutes about 80% of the whole genome, in Helicobacter pylori 77 and 46% in Streptococcus pneumoniae [ 35 ]. On the other hand, the size of the core and essential genome was estimated to be composed of 404 genes [ 36 ], a number comparable to other bacterial species, such as Pseudomonas aeruginosa (321 genes [ 37 ]) and Yersinia pestis (about 500 genes [ 38 ]).…”
Section: Discussionmentioning
confidence: 99%